A stimuli-responsive, superporous and non-toxic smart hydrogel from seeds of mugwort (Artemisia vulgaris): stimuli responsive swelling/deswelling, intelligent drug delivery and enhanced aceclofenac bioavailability. Issue 34 (27th May 2020) - Farid-ul-Haq, Muhammad; Hussain, Muhammad Ajaz; Haseeb, Muhammad Tahir; Ashraf, Muhammad Umer; Hussain, Syed Zajif; Tabassum, Tahira; Hussain, Irshad; Sher, Muhammad; Bukhari, Syed Nasir Abbas; Naeem-ul-Hassan, Muhammad
Abstract : Artemisia vulgaris hydrogel (AVH) was evaluated as a smart material for the development of sustained and intelligent drug delivery system for NSAIDs. AVH appeared to be a non-toxic material for possible biomedical and pharmaceutical applications. Abstract : Artemisia vulgaris seeds extrude hydrogel (AVH), which shows extraordinary swelling in water, at pH 6.8, and 7.4, which follows second-order kinetics. AVH exhibits reversible swelling/deswelling in ethanol and normal saline as well at pH 7.4 and pH 1.2. Therefore, AVH shows stimuli-responsiveness in different physiological conditions, solvents, and electrolytes. The superporous nature of AVH in swollen/freeze-dried sculpture is exposed in their SEM micrographs. AVH-based aceclofenac tablet formulations offer sustained-release under simulated conditions of the gastrointestinal tract (GIT) in terms of pH and transit time. Pharmacokinetic studies also show the delay and prolonged plasma concentration with t max of 8 h, therefore, such formulations can be used to enhance the bioavailability of aceclofenac. The swelling behavior of the AVH tablet is also assessed using MRI. The in vivo fate of the AVH tablet is monitored by X-ray during the transit through the GIT. Acute toxicity studies of AVH indicate the absence of any toxicity which reveals the safety profile of AVH. Therefore, AVH can be used for oral, topical and ophthalmic drug delivery systems. These results establish the potential of AVH as a stimuli sensitive, pH-dependent, and sustained-release biomaterial for targeted drug delivery.